2001
DOI: 10.1107/s0108767300015774
|View full text |Cite
|
Sign up to set email alerts
|

Strength tuning of multiple waves in crystals

Abstract: In this work, the linear polarization of synchrotron radiation is explored as a tuning key for the strength of the simultaneously diffracted X-ray waves in crystals. The relative strength of the waves has been de®ned by the re¯ectivities of the Bragg re¯ections involved in each multiple-diffraction case and it has limited the applicability of the multiple-diffraction phenomenon. With a proper choice of the wavelength and the polarization direction of the incident synchrotron radiation, it is demonstrated how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 26 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…The peak in reflection in s-polarization roughly corresponds to the avoided crossing of the s-bands, suggesting that it is related to multiple diffraction involving the (200) planes. One possible explanation for this different behavior can be found from the theory of multiple X-ray diffraction [22]: Coherent scattering of p-polarized EM waves is forbidden by polarization if θ=45°, since according to Maxwell's equation an accelerated charge does not emit in the direction of its acceleration. (In optics this is more commonly known as Brewster angle effect.)…”
Section: Discussionmentioning
confidence: 99%
“…The peak in reflection in s-polarization roughly corresponds to the avoided crossing of the s-bands, suggesting that it is related to multiple diffraction involving the (200) planes. One possible explanation for this different behavior can be found from the theory of multiple X-ray diffraction [22]: Coherent scattering of p-polarized EM waves is forbidden by polarization if θ=45°, since according to Maxwell's equation an accelerated charge does not emit in the direction of its acceleration. (In optics this is more commonly known as Brewster angle effect.)…”
Section: Discussionmentioning
confidence: 99%
“…1) and another with a much weaker secondary wave ͑R 0.332͒ from the 226 1400 reflections. The latter is a very extreme case since at x 50.8 ± the 226 reflection is a polarization forbidden reflection (y d 0͒ [15]. Only the Auf hellung effect will be observed at this polarization.…”
mentioning
confidence: 95%
“…For practical applications, these techniques are time-consuming and limited to a few n-BDs that present good phase sensitivity. Very recently, several authors have demonstrated that the linear polarization of synchrotron radiation can be used to change the relative strength of multiple diffracted waves [14,15] and/or improve phase sensitivity in some cases [16]. Polarization resolved n-BD has also been considered for enhancing phase sensitivity [17].…”
mentioning
confidence: 99%
See 2 more Smart Citations